2018
DOI: 10.1111/cpr.12434
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine promotes mesenchymal stem cell homing in noise‐induced injured cochlea through PI3K/AKT pathway

Abstract: Pre-conditioning of MSCs by DFO before transplantation can improve stem cell homing in the damaged cochlea through PI3K/AKT pathway activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
(85 reference statements)
1
22
0
Order By: Relevance
“…We also found that BMSC-CM inhibited neuron and glial cell death and improved functional recovery. Cantinieaux D showed the use of BMSC-CM to prevent neuron apoptosis, activation of macrophages and motor improvement in the rat's SCI model due to neurotrophic secretions of BMSC, which were consistent with our results (14). Other researchers also found that the CM of some other types of stem cells, such as the umbilical cord and Embryonic stem cells, had similar effects to BMSC on spinal cord injury improvement (15).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We also found that BMSC-CM inhibited neuron and glial cell death and improved functional recovery. Cantinieaux D showed the use of BMSC-CM to prevent neuron apoptosis, activation of macrophages and motor improvement in the rat's SCI model due to neurotrophic secretions of BMSC, which were consistent with our results (14). Other researchers also found that the CM of some other types of stem cells, such as the umbilical cord and Embryonic stem cells, had similar effects to BMSC on spinal cord injury improvement (15).…”
Section: Discussionsupporting
confidence: 87%
“…Prescription of medications that decrease infl ammatory infi ltration and can inhibit the injury expansion (11). Methylprednisolone (MP) is a corticosteroid that inhibit lipid peroxidation and reduces infl ammatory cell and cytokine at the site of injury and improve the perfusion of the spinal cord and reduce the infl ux of neuronal calcium (12,13,14) The purpose of this experimental study is evaluation of the effect of BMSCs Condition Media and MP in TGF-β expression and functional recovery after acute spinal cord injury in adult wistar rat.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of this pathway can be directly related to the increase of Ad-MSCs migration and homing of cells towards the injured tissues, as it had been demonstrated in many studies that chemokine and chemokine receptors have essential role in stem cell and cancer cell migration (Liu et al 2018;Mishan et al 2015Mishan et al , 2016. Similar to a study that DFX preconditioning significantly increased the homing ability of MSCs into injured area through increasing the expression of PI3K/AKT, HIF-1a and CXCR4 (Peyvandi et al 2018). Moreover, in a study, it was demonstrated that pre-treatment with VPA before transplantation enhances the therapeutic benefits of bone marrow MSCs (BMSCs) in terms of greater cell migration and better neurological outcomes through increasing the expression of CXCR4 after traumatic acute spinal cord injury (SCI) in animal models (Chen et al 2014).…”
Section: Discussionmentioning
confidence: 77%
“…In comparison with untreated MSCs, the homing of DFO‐treated MSCs in injured rat cochlea was increased. These effects of primed DFO MSCs were confirmed with a PI3K inhibitor (Peyvandi et al, 2018).…”
Section: Modulation Of Mscs For Therapeutic Purposementioning
confidence: 80%